Serum IL-1?, IL-2, IL-6, and IL-8 Levels in Schizophrenia Subtypes - Kuloglu, Murat; Bayik, Yilmaz; Unal, Ahmet; Gecici, Omer; Ustundag, Bilal (Kure Iletisim Grubu A S, 2011)
Serum IL-1 beta, IL-2, IL-6, and IL-8 levels in schizophrenia subtypes Objective:The cytokines are considered to be an important topic in immunological studies of schizophrenia. In this clinical study IL-1 beta, IL-2, IL-6, and IL-8 levels were compared among schizophrenia subtypes and a control group. Method: Sixty-one patients diagnosed with schizophrenia according to the DSM-IV and 25 healthy controls were studied. The clinical and demographic information form was completed for all patients. Morning venous blood samples were collected between 8:00 and 9:00 AM from the patients and the control group. The serum IL-1 beta, IL-2, IL-6 and IL-8 levels were assessed by the ELISA method. Results: Serum IL-1 beta levels were statistically higher than the control group in patients with paranoid schizophrenia and the disorganized subtype (p<0.05). According to IL-2 levels there was a significant difference between the residual, paranoid, disorganized, and undifferentiated subtypes and the control group (p<0.01). Based on IL-6 levels a mild significant difference was observed between the residual schizophrenia subtype and the control group (p<0.05), but this difference was much more significant in the disorganized and paranoid subtypes compared to the control group (p<0.001). Serum IL-8 levels in patients with paranoid schizophrenia were statistically significantly higher than the disorganized, undifferentiated or residual subtypes, and the control group (p<0.001). Conclusions: Our results show some immunological changes in schizophrenia and these changes may be related to clinical differences in the sub-types of schizophrenia.
Şizofreni alt tiplerinde serum IL-1?, IL-2, IL-6 ve IL-8 düzeyleri
Keywords: Schizophrenia; cytokine; interleukin